Evaluation of Mandibular Third Molar Position by Using Space-Width Ratio Method - Mohamed, Istabraq M.; Ghaib, Nidhal H. (Journal of Baghdad College of Dentistry, 2016)
Background: The prediction of changes in the mandibular third molar position and eruption is an important clinical concern because third molar retention may be beneficial for orthodontic anchorage. The aims of this study were to assess the mandibular third molar position by using medical CT scan and lateral reconstructed radiograph and evaluate gender differences. Materials and Methods: The sample of present study consisted of 39 patients (18 males and 21 females) with age range 11-15 years who were attending at Al-Suwayra General Hospital/ the Computerized Tomography department. The distance from anterior edge of ramus to distal surface of permanent mandibular second molar and mesio-distal width of developing mandibular third molar were measured in both three dimensional volumetric and two dimensional CT derived lateral images. The statistical analyses included: means, standard deviations. Paired t-test was used to compare between the two methods and independent t-test was used in verifying the genders difference. Results: The results showed that there was high significant method difference between 3D CT and 2D image and gender differences were observed in values of linear measurements of present study, as males showed higher mean values than females. Conclusion: There is high accuracy of measurement on CT images, so C.T. scan is advisable during the diagnosis and treatment plan of orthodontic cases.